Noonan Syndrome: An Underestimated Cause of Severe to Profound Sensorineural Hearing Impairment. Which Clues to Suspect the Diagnosis?. Issue 8 (September 2017) - Ziegler, Alban; Loundon, Natalie; Jonard, Laurence; Cavé, Hélène; Baujat, Geneviève; Gherbi, Souad; Couloigner, Vincent; Marlin, Sandrine
Abstract : Objective: To highlight Noonan syndrome as a clinically recognizable cause of severe to profound sensorineural hearing impairment. Study Design: New clinical cases and review. Setting: Patients evaluated for etiological diagnosis by a medical geneticist in a reference center for hearing impairment. Patients: Five patients presenting with confirmed Noonan syndrome and profound sensorineural hearing impairment. Interventions: Diagnostic and review of the literature. Results: Five patients presented with profound sensorineural hearing impairment and molecularly confirmed Noonan syndrome. Sensorineural hearing impairment has been progressive for three patients. Cardiac echography identified pulmonary stenosis in two patients and was normal for the three other patients. Short stature was found in two patients. Mild intellectual disability was found in one patient. Inconspicuous clinical features as facial dysmorphism, cryptorchidism, or easy bruising were of peculiar interest to reach the diagnosis of Noonan syndrome. Conclusion: Profound sensorineural hearing impairment can be the main feature of Noonan syndrome. Associated features are highly variable; thus, detailed medical history and careful physical examination are mandatory to consider the diagnosis in case of a sensorineural hearing impairment.